2003
DOI: 10.1107/s0907444903006498
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray crystallographic analysis ofD-phenylglycine aminotransferase fromPseudomonas stutzeriST201

Abstract: d-Phenylglycine aminotransferase (d-PhgAT) catalyzes the reversible transamination of d-phenylglycine to l-glutamate with 2-oxoglutarate as the amino-group acceptor. Crystals of substrate-free Pseudomonas stutzeri d-PhgAT bound to the cofactor pyridoxal-5'-phosphate (PLP) were obtained by the hanging-drop vapour-diffusion method using ammonium sulfate as a precipitant. The crystals belong to space group P3(1)21 or P3(2)21, with unit-cell parameters a = b = 75.155, c = 147.554 A. The asymmetric unit contains on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The overexpression and purification of recombinant D-PhgAT were done as previously described [3,11]. Briefly, overnight culture of the recombinant E. coli tuner (DE3) pLysS was used to inoculate 250 ml of Luria Bertani broth (Difco) containing 100 µg/ml of ampicillin (Bio Basic Inc., Canada) and 34 µg/ml of chloramphenicol (Sigma-Aldrich Co. LLC, USA), followed by incubation at 37°C and 200 rpm until OD 600 of 0.6 was reached.…”
Section: Overexpression and Purification Of Different Variants Of Recmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression and purification of recombinant D-PhgAT were done as previously described [3,11]. Briefly, overnight culture of the recombinant E. coli tuner (DE3) pLysS was used to inoculate 250 ml of Luria Bertani broth (Difco) containing 100 µg/ml of ampicillin (Bio Basic Inc., Canada) and 34 µg/ml of chloramphenicol (Sigma-Aldrich Co. LLC, USA), followed by incubation at 37°C and 200 rpm until OD 600 of 0.6 was reached.…”
Section: Overexpression and Purification Of Different Variants Of Recmentioning
confidence: 99%
“…1), was first reported in 1997 [24]. Crystallography and 3D studies revealed that D-PhgAT is a homodimer enzyme, where each monomer possesses three domains namely a C-terminus, an N-terminus, and a cofactor binding domain with 453 amino acid residues and 47.5 kDa molecular mass [11]. Owing to its stereo-inverting property and the ability to utilize L-glutamic acid as a cheap amino group donor, D-PhgAT is an invaluable catalyst in the single-step synthesis of D-Phg and D-4hydroxyphenylglycine (D-4-OHPhg), which are essential side-chain moieties for manufacturing semisynthetic antibiotics in the penicillin and cephalosporin families.…”
Section: Introductionmentioning
confidence: 99%
“…The hypothetical ancestral enzyme might also have had some preference towards the amino group acceptor; in fact, in Fig. 6 most of the tree branches closest to the root represent α-KGspecific ATs (DHNEAT, NEAT, LAT and D-FGAT: for the last enzyme, a PDB-deposited crystal structure exists (2CY8; [87]), which however does not contain bound PLP and lacks other structural details).…”
Section: Inferences On the Evolution Of At-ii Enzymesmentioning
confidence: 97%
“…once the scope of this aminotransferase is broadened to other classes of D-amino acids by protein engineering -a process which will certainly benefit from the structural information that recently became available [206].…”
Section: Aminotransferase-catalyzed Production Of D-a-h-a-amino Acidsmentioning
confidence: 99%